'All Avatars Aren't We': Football and the experience of football-themed digital content during a global pandemic. (June 2022) - Crawford, Garry; Fenton, Alex; Chadwick, Simon; Lawrence, Stefan
This paper explores the contemporary nature of association football consumption. In particular, we argue that the coronavirus 2019 pandemic reveals the contemporary and particular nature of the relationship between football and its supporters, which is increasingly focused on the consumption of themed digital participatory experiences. During this pandemic, what fans missed was not only live football, but also the sporting 'experience' and the opportunities for participation that this provides. Hence, here we saw fans, clubs and media providers employing new digital technologies to create themed experiences that facilitated (and mediated) participation and interaction. Following Žižek (2014), we suggest that the coronavirus 2019 pandemic can be understood as a global mega event that creates a seismic, reality alerting schism, whose aftermath requires new ontologies and theories. Our response is to utilise a number of key and illustrative examples and to offer a new synthesis of theories and literatures, most notably, on the experience society, theming, participatory culture, neoliberalism and digital culture. This new context and (re)combination of theories then provides a new, and essential, perspective that reveals a great deal about the contemporary nature of the sport, what fans buy into, and also, how this may change post pandemic.